2015
DOI: 10.4254/wjh.v7.i10.1337
|View full text |Cite
|
Sign up to set email alerts
|

Liver steatosis in hepatitis C patients

Abstract: would affect HCV patients who are also obese or diabetics. In fact, several genotypes exert metabolic effects which overlap with some of those observed in the metabolic syndrome. In this review we will analyse the pathogenic pathways involved in the development of steatosis in HCV patients. Several cytokines and adipokines also become activated and are involved in "pure" steatosic effects, in addition to inflammation. They are probably responsible for the evolution of simple steatosis to steatohepatitis, makin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 105 publications
1
7
0
Order By: Relevance
“…There is an increased prevalence of steatosis in patients with chronic hepatitis C, but it is not firmly established whether fat deposition is directly due to the virus itself, or whether it is secondary to liver dysfunction caused by chronic infection. [31][32][33] In this study, as was previously reported, 29 there was no demonstrable effect of the presence of fat on SWE liver parenchymal stiffness values in either the native or the transplanted livers. We speculate that the speed of the shear waves in fat is similar to that in normal liver tissue.…”
Section: Infection-mediated Inflammation Usually Precedes Fibrosis Andsupporting
confidence: 82%
“…There is an increased prevalence of steatosis in patients with chronic hepatitis C, but it is not firmly established whether fat deposition is directly due to the virus itself, or whether it is secondary to liver dysfunction caused by chronic infection. [31][32][33] In this study, as was previously reported, 29 there was no demonstrable effect of the presence of fat on SWE liver parenchymal stiffness values in either the native or the transplanted livers. We speculate that the speed of the shear waves in fat is similar to that in normal liver tissue.…”
Section: Infection-mediated Inflammation Usually Precedes Fibrosis Andsupporting
confidence: 82%
“…Liver pathologies, such as steatosis, are affected by many factors . Here, we provide insights into the propagation of HCV and steatosis caused by chronic HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis C virus (HCV) is a major cause of chronic liver disease and affects over 185 million individuals worldwide 1 . Persistent HCV infection is a leading cause of chronic hepatitis, liver cirrhosis, and even hepatocellular carcinoma 2 3 . Although HCV infections can be partially combatted by the new treatment regimens with direct-acting antiviral drugs (DAAs), the high specificity of DAAs against their viral targets might result in emergence of antiviral resistance, and even these regimens are costly which might also lead to a restricting societal benefit 4 .…”
mentioning
confidence: 99%